632 IX Steady Navier–Stokes Flow in Bounded Domains
ν(∇v
1
, ∇ϕ) = (v · ∇ϕ, v) , for al l ϕ ∈ D(B) , v ∈ H
1
t
(B)
ν(∇v
2
, ∇ϕ) = −(f, ϕ) for all ϕ ∈ D(B) , v ∈ W
2,q
(B) ∩ H
1
q
(B) .
(IX.5.50)
Clearly, the function Φ : = v−v
1
−v
2
satisfies (∇Φ, ∇ϕ) = 0, for all ϕ ∈ D(Ω),
and, consequently, in view of the prop erties of v, v
1
, v
2
and of Theorem IV.4.3,
we find Φ ∈ C
∞
(B). Furthermore, by Theorem IV.6.1(a), v
2
exists and, by
the embedding Theorem II. 3.4, v
2
∈ W
1,2
(B). Therefore, to show (IX.5.49),
it is enough to show that v
1
∈ W
1,2
(B). We shall prove this by means of
a recurrence argument based on a repeated use o f Theorem IV.6.1(b) and
of the embedding Theorem II .3.4. Actually, from the former theorem and
(IX.5.45)
1
we can take t ≡ t
0
= s
0
/2, which, by Theorem II.3.4 and the fact
that s
0
∈ (2, 4), implies v ∈ L
2t
0
/(2−t
0
)
(B). Thus, again by Theorem IV.6.1,
we may take t ≡ t
1
= t
0
/(2 −t
0
), which, in turn, by Theorem II.3.4 furnishes
v ∈ L
2t
1
/(2−t
1
)
(B), and so on. We thus obtain the following recurrence relation
for the exponents t
k
:
t
k+1
=
t
k
2 − t
k
, k ∈ N , t
0
= s
0
/2 . (IX.5.51)
We notice that, since by assumption t
0
> 1 + η, for some positive η, the
sequence {t
k
} is increasing, and so, in particular, t
k
> 1 + η, for all k ∈ N. We
claim that there is k ∈ N such that t
k+1
= 2. By assuming the contrary, we
would have t
k
< 2, for all k ∈ N, and so, due to the fact that {t
k
} is increasing,
there is t
∗
> 0 such tha t t
k
→ t
∗
as k → ∞. However, by taking the limit
k → ∞ in (IX.5. 51), we would find t
∗
= 1, which furnishes a contradiction. As
a consequence, (IX.5.49) is proved. By an argument entirely analogous to that
used to show (IX.5.38), we show f ∈ W
−1,2
(ω) for all bo unded domains ω with
ω ⊂ Ω. Thus, from (IX.5.51) and Lemma IX.2.1, we deduce p ∈ L
2
loc
(Ω). T his
latter property along with (IX.5.51) and (IX.5.48)
3,4
, allows us to conclude
F ∈ L
q
(B
0
), g ∈ W
1,q
(B
0
), q ∈ (1, 2), so that by Lemm a IX.5.1 and (IX.5.49)
we prove (IX.5.46) for n = 2. We next consider the case n = 3. If q ∈ (1, 3/2],
from (IX.5.45) and (IX.5.47) we easily find tha t
F ∈ L
q
(B
0
) , g ∈ W
1,q
(B
0
) , (IX.5.52)
with q = q, and so, by Lemma IX.5.1, the property (IX.5.46) follows for the
above va lues of q. If q ∈ (3/2, 3), again by (IX.5.45), we find tha t F , g satisfy
(IX.5.52) wi th q = 3/2, which, in turn, by Lemma IX.5.1 and the arbitrari ness
of Ω
0
implies (v, p) ∈ W
2,3/2
loc
(Ω)×W
1,3/2
loc
(Ω). From this latter property, by the
embedding Theorem II.3 .4, we infer (v, p) ∈
W
1,3
loc
(Ω) ∩ L
∞
loc
(Ω)
×L
3
loc
(Ω).
Thus, we deduce the validity of (IX.5.52), with q = q, q ∈ (3/2, 3), which, by
Lemma IX.5.1, concludes the proof of (IX. 5.46), in the case n = 3. If n ≥ 4 ,
suppose first q ∈ (1, n/3). Then, from (IX.5.45)
4
, we find r/2 > q, which
implies (IX.5.52), with q = q, and so, in turn, (IX.5.46) for these values of q.
If q ∈ [n/3, n/2], then, by (IX.5.45)
3
, we may take q = q in (IX.5 .52), which,